The Effectiveness of Surgical Methods for Trismus Release at Least 6 Months After Head and Neck Cancer Treatment: Systematic Review - Smeets, Maximiliaan; Croonenborghs, Tomas-Marijn; Van Dessel, Jeroen; Politis, Constantinus; Jacobs, Reinhilde; Bila, Michel (Frontiers in Oral Health, 2022)
Introduction The objective of this systematic review with meta-analysis was to obtain an overview on the different surgical treatment modalities of severe trismus after head and neck squamous cell cancer treatment. Materials and Methods An electronic literature database search was conducted in Medline, Embase, Cochrane, and Web of Science to determine articles published up to September 2020. Two observers independently assessed the identified papers for eligibility according to PRISMA guidelines. The quality was evaluated using the Newcastle-Ottawa scale. A meta-analysis of the maximal mouth opening (MMO) was performed using a mixed-effect model. Results A total of 8607 unique articles were screened for eligibility, 69 full texts were reviewed, and 3 studies were selected based on the predetermined inclusion and exclusion criteria. Three treatment strategies were identified for trismus release (1) free flap reconstruction (FFR), (2) coronoidectomy (CN), and (3) myotomy (MT). There was a clear improvement for all treatment modalities. A quantitative analysis showed a beneficial effect of CN in comparison with FFR and MT (P < .01*). An increased gain in MMO after trismus release was found if no primary resection was performed (P = .014*). The three studies included in the meta-analysis all had an intermediate risk of bias. Conclusion Currently available reports suggest a low threshold for performing a CN compared with FFR and MT. There is a need for high-quality randomized controlled trials with carefully selected and standardized outcome measures.